Pembacaan Perspektif Makkiy-Madaniy atas Kisah Nabi Lut dalam Al-Qur’an - Ali, Rijal; Rahmatina, Nada; Anggraini, Tri Faizah (SUHUF, 2024)
This research aims to reveal the relationship between the Quranic text and the story of the Prophet Lut and his people within the early Arab prophetic society. Additionally, it explores the purpose behind presenting this story to the early Arab society known to have no sexual deviations. This research uses library research with qualitative research methods to achieve this purpose. This research focuses on the verses describing the story of the Prophet Lut and his people by referring to Theodor Noldeke’s Meccan-Medinan chronological periodization to obtain the characteristics of each period. This research finds that the story of the Prophet Lut falls into the first, second, and third Meccan periods. The development of Prophet Lut and his people’s narrative in each period aligns with the development of the needs and challenges of the Prophet Muhammad’s preaching. Homosexuality occupied the same position as the shirk in early Arab society because it was against human nature. The story of the Lut people was evidence of God’s power in destroying people who disobey and violate human nature.